NURBS Reconstruction and Optimization Method for the Tooth Surface after Simulation Process of Spiral Bevel Gear - Li Yunsong; Adayi·Xieeryazidan; Ding Han (Jixie chuandong)
For lower accuracy of tooth surface of outputted model after simulation process for spiral bevel gear,some methods cubic NURBS reconstruction and optimization of tooth surface are proposed by combining with the advantages and features of the Non- Uniform B- Spline curves（ NURBS） in CAD / CAM. Firstly,on the basis of analyzing the tooth surface shape from simulation processing,the initial data points are extracted and made their optimal selection. The transverse tooth profile including work,fillet,tooth root part as v line,similarly tooth fillet line as u line,the NURBS curve fitting is respectively carried out. Then,based on the basic curves by fitting,the NURBS reconstruction of tooth surfaces for spiral bevel gears is carried out by using the skinning method. Finally,the reconstruction of tooth surface as the base surface,a variety of tooth surface optimization schemes based on Newton iteration and the least squares method are proposed,so as to complete the precise fitting of the tooth surfaces. Though making compared accuracy analysis of the relevant numerical examples,the proposed method for reconstruction and optimization have a good validity.